Growth of centimeter-scale high-quality In2Se3 films for transparent, flexible and high performance photodetectors. Issue 34 (17th August 2016) - Zheng, Z. Q.; Yao, J. D.; Yang, G. W.
Abstract : A centimeter-scale In2 Se3 film has been achieved via PLD and high-sensitivity photodetection has been demonstrated. Abstract : High-sensitivity photodetectors are of great importance to extensive applications. However, thus far, photodetectors integrating transparency, flexibility, broadband response and competitive responsivity are quite rare. Herein, we demonstrate that photodetectors fabricated with pulsed-laser deposition (PLD) grown centimeter-scale high quality In2 Se3 films on various substrates are capable of superior photoresponse. In particular, the fabricated device on a transparent polyimide (PI) substrate possesses flexible and transparent properties. In addition, it exhibits broadband photoresponse ranging from 254 to 1064 nm and a high detectivity reaching 6.02 × 10 11 cm Hz 1/2 W −1 at 532 nm. The responsivity and the external quantum efficiency are 20.5 A W −1 and 4784%, respectively, plus it shows a fast response time of 24.6 ms for the rise and 57.4 ms for the decay. Importantly, the responsivity of the device exhibits a linear dependence on the bias voltage, providing smooth modulation for multifunctional photoelectrical applications. We establish that the direct bandgap nature of In2 Se3 and good Ohmic contact between In2 Se3 and indium tin oxide (ITO) electrodes are responsible for such excellent performance. This study unambiguously reveals that these PLD-grown In2 Se3 films possess the potential to be applied for versatile optoelectronic systems.